2017
DOI: 10.1161/jaha.117.006345
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐Derived Factor V Is a Critical Mediator of Arterial Thrombosis

Abstract: BackgroundCoagulation factor V (FV) plays a key role in hemostasis, is present in plasma and platelets, and has both pro‐ and anticoagulant properties; however, the contribution of platelet‐derived FV to arterial thrombosis remains undetermined.Methods and ResultsUsing transgenic mice with various levels of FV gene expression that was restricted to the plasma or platelets, the roles of platelet FV were evaluated in the regulation of arterial thrombosis and platelet activation. Mice with higher levels of platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
1
13
0
2
Order By: Relevance
“…In addition, the authors found that the addition of normal platelets reduced the time required to initiate clotting, suggesting an important role for platelet FV release in initiating thrombin generation. As shown in our previous study, mice with lower platelet FV levels exhibit slower thrombotic occlusion of the carotid artery after injury (18). However, based on our current findings, mice with lower platelet FV develop more lung metastases due to increased adhesion of tumor cells to endothelial cells.…”
Section: Figure 3 | Plasma Fv Level and Tfpiα Expression In Plateletssupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, the authors found that the addition of normal platelets reduced the time required to initiate clotting, suggesting an important role for platelet FV release in initiating thrombin generation. As shown in our previous study, mice with lower platelet FV levels exhibit slower thrombotic occlusion of the carotid artery after injury (18). However, based on our current findings, mice with lower platelet FV develop more lung metastases due to increased adhesion of tumor cells to endothelial cells.…”
Section: Figure 3 | Plasma Fv Level and Tfpiα Expression In Plateletssupporting
confidence: 80%
“…However, researchers have not yet determined whether the levels of FV are associated with tumor progression and metastasis. Using transgenic mice that express different levels of the FV gene in either plasma or platelets (17), we recently identified a critical role for platelet-derived FV in the regulation of arterial thrombosis through platelet activation (18). In the current study, we evaluated the role of FV from different sources in metastasis.…”
Section: Introductionmentioning
confidence: 96%
“…Platelet-derived factor V may be an important determinant of local prothrombinase formation, driving atherogenesis (Ren et al 2017). Additional factors that are secreted by platelets are tissue factor (TF) (the origin still somewhat controversial) and protein disulfide-isomerase (PDI) that acts to de-encrypt TF in an active conformation.…”
Section: Platelets and Extracellular Vesiclesmentioning
confidence: 99%
“…Результаты экспериментального исследования на трансгенных мышах позволяют предположить, что V фактор свертывания тромбоцитарного происхождения представляет собой ключевой медиатор развития артериального тромбоза in vivo, способствующий активации тромбоцитов и повышению свертываемости крови [27]. Такой фактор участвует в соединении протромбиназного комплекса с Ха фактором в месте разрыва атеросклеротической бляшки.…”
Section: возможные механизмы положительного влияния приема низких дозunclassified
“…В результате образуется большое количество тромбина на поверхности активированного тромбоцита и по механизму обратной связи отмечается ранняя активация свертывающего каскада. Считается, что прямые ингибиторы тромбина, в частности дабигатран, могут не приводить к такому же уменьшению образования тромбина, которое вызывают ингибиторы Ха фактора [27,28]. Такую концепцию подтверждают данные о том, что V фактор свертывания крови человека высвобождается из α-гранул активированных тромбоцитов при их частично активированном состоянии, а Ха фактор оказывает в 50-100 раз большее влияние на активацию выделяемого тромбоцитами V фактора по сравнению с тромбином.…”
Section: возможные механизмы положительного влияния приема низких дозunclassified